Talent Attraction And Organizational Competitiveness in Manufacturing Companies in Lagos, Nigeria - Nuha Salihu AREMU; Oluseyi Adetunji SHADARE; Jimoh Rafiu AMOSA (Journal of Human Resource Management, 2023)
Purpose- The main focus of the study is to examine how talent attraction dimensions such as employee value proposition, employer branding, Job flexibility and recruitment and selection affect organizational competitiveness in manufacturing firms in Lagos State, Nigeria. Methodology- The study adopted a survey-based research design. The permanent staff of the selected ten (10) food, beverages, and tobacco manufacturing firms in Lagos State made up the population of the study. The respondents consist of 368 employees which represent the sample size of the study. Data was obtained through the use of questionnaire. Relative Important Index (RII) and Multivariate linear regression was used for data analysis with aid of SPSS version 26. Findings- The result revealed a strong effect of talent attraction variables such as employee value proposition with (β=0.611, t= 7.451, p<0.05); Job flexibility with (β=0.505, t=9.182, p< 0.05); employer branding with (β=0.434, t= 9.607, p <.0.05) and recruitment and selection with (β=0.401, t=6.481, p <.0.05) on organizational competitiveness. Limitations of the study-The scope of this study was limited to food, beverages and tobacco manufacturing subsector operating only within the territory of Lagos state, Nigeria. Furthermore, the study looked at talent attraction variables which is only a component of talent management strategies. Practical Implication-The manufacturing companies, especially the ones in food, beverages and tobacco manufacturing sub-sector should consider talent attraction strategies as a viable tool for identifying and attracting skilful and competent staff to fill vacant position. This is critical to the attainment of present and future organizational objectives as well as gaining competitive advantage. Originality/Value- This study makes a clear understanding of talent attraction and its immense contribution to organizational competitiveness and performance. It also provided a basis for future researcher to explore more on the dynamics of talent attraction in the field of human resource management.